Emergency medical equipment on board German airliners - Hinkelbein, Jochen; Neuhaus, Christopher; Wetsch, Wolfgang A.; Spelten, Oliver; Picker, Susanne; Böttiger, Bernd W.; Gathof, Birgit S. (Journal of travel medicine, 2014)
AbstractBackground. Medical emergencies often occur on commercial airline flights, but valid data on their causes and consequences are rare. Therefore, it is